Hubungan antara Pengetahuan tentang Kanker Serviks dengan Pemeriksaan IVA - Juminten Saimin; Sri Hasriani Haris; Fedelia Raya; Satrio Wicaksono (Halu Oleo University, 2018)
Introduction: Cervical cancer is the most of gynecological malignancies that cause death, especially in developing countries. The behavior to conduct a medical examination is determined bypredisposing, supporting and reinforcing factors. Predisposing factors for carrying out medical examinations include knowledge and attitude. Objective : To determine corrrelation between knowledge about cervical cancer and VIA examination in Puskesmas Lepo-Lepo. Method :This study was analytic observational design with cross sectional method. The study was conducted in Puskesmas Lepo-Lepo with total samples was 347 women. Samples were taken using proportional stratified random sampling. Data were analyzed using Chi-Square with significancy value < 0.05. Result: The most participant in urban and rural areas was the age group 31-40 years old (38,6%), high school level (44,4%), as housewife (67,8%), have less knowledge about cervical cancer (70,9%) and got information about cervical cancer from the mass media (40,6%). There was correlation between knowledge about cervical cancer and VIA examination in Puskesmas Lepo-Lepo (p = 0.000). Conclusion: There was a significant correlation between knowledge about cervical cancer and VIA examination in Puskesmas Lepo-Lepo.Keywords: Cervical Cancer, Knowledge, Visual Inspection with Acetic Acid